(untitled) (GAIMS Journal of Medical Sciences, 2023)
Cloacal exstrophy is a rare condition that occurs during the prenatal development of the lower abdominal wall. Cloacal exstrophy is also known as OEIS Syndrome because of the four features that are typically found together: Omphalocele, Exstrophy of the bladder and rectum, Imperforate anus, Spinal defects.1 We describe a case of 29-year-old female with 3 months’ gestation, her USG showed rudimentary right lower limb and anterior abdominal wall defect for which pregnancy was terminated and fetal autopsy was performed. This is a first case report from our institute in which the fetal autopsy finding showed features of OEIS syndrome.